A microarray analysis of the rice transcriptome and its comparison to Arabidopsis - Ma, Ligeng; Chen, Chen; Liu, Xigang; Jiao, Yuling; Su, Ning; Li, Lin; Wang, Xiangfeng; Cao, Mengliang; Sun, Ning; Zhang, Xiuqing; Bao, Jingyue; Li, Jian; et al. (Genome Research, 2005)
Arabidopsis and rice are the only two model plants whose finished phase genome sequence has been completed. Here we report the construction of an oligomer microarray based on the presently known and predicted gene models in the rice genome. This microarray was used to analyze the transcriptional activity of the gene models in representative rice organ types. Expression of 86% of the 41,754 known and predicted gene models was detected. A significant fraction of these expressed gene models are organized into chromosomal regions, about 100 kb in length, that exhibit a coexpression pattern. Compared with similar genome-wide surveys of the Arabidopsis transcriptome, our results indicate that similar proportions of the two genomes are expressed in their corresponding organ types. A large percentage of the rice gene models that lack significant Arabidopsis homologs are expressed. Furthermore, the expression patterns of rice and Arabidopsis best-matched homologous genes in distinct functional groups indicate dramatic differences in their degree of conservation between the two species. Thus, this initial comparative analysis reveals some basic similarities and differences between the Arabidopsis and rice transcriptomes.
10.1101/gr.3657405